New and traditional media influence of Muslim students’ perception on selected Islamic issues: A comparative study - Wok, Saodah; Wan Mohd Ghazali, Wan Norshira (2011)

(untitled)
For a new medium, the Internet use is being pervasive among students and it could influent students’ perception on various issues. However, the traditional media (TV and newspapers) are standing tall among the existing media. As such, this study tries (1) to find out the demographic characteristics of the Muslim students in the study in relation to their media use; (2) to determine the level of usage, trust, and influence on the Internet, TV, and newspapers among heavy users; (3) to explore heavy users’ (new and traditional media) perception level on some selected Islamic issues; and (4) to study the relationships between heavy users’ trust and influence on the new and traditional media with selected Islamic issues. Using the premise of the Dependency Theory (Ball-Rokeach and De Fleur, 1976), the study probed the heavy users of Internet, TV, and newspapers among a total of 369 Muslim students in Malaysia. Data collected through survey research were analyzed using SPSS WIN 16 to answer the objectives of the study.